2011
DOI: 10.1111/j.1558-5646.2011.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of Pheromone Production in Signaling Female Moths

Abstract: A secondary sexual character may act as an honest signal of the quality of the individual if the trait bears a cost and if its expressionis phenotypically condition dependent. The cost of increasing the trait should be tolerable for individuals in good condition but not for those in a poor condition. The trait thus provides an honest signal of quality that enables the receiver to choose higher quality mates. Evidence for sex pheromones, which play a major role in shaping sexual evolution, inflicting a signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 113 publications
6
123
1
2
Order By: Relevance
“…Although many empirical studies have measured the percentage of females calling (e.g., Webster and Cardé 1982;Babilis and Mazomenos 1992;Kamimura and Tatsuki 1993;Ming et al 2007), more information on their spatial arrangement could prove useful. Females can potentially use cues other than their own mating status to adjust signaling effort: if females can perceive the signals of competing females, there is potential for more complex signaling strategies than the ones modeled by us (Harari et al 2011). Experimental manipulation of juvenile environments can also prove informative (Gibbs et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although many empirical studies have measured the percentage of females calling (e.g., Webster and Cardé 1982;Babilis and Mazomenos 1992;Kamimura and Tatsuki 1993;Ming et al 2007), more information on their spatial arrangement could prove useful. Females can potentially use cues other than their own mating status to adjust signaling effort: if females can perceive the signals of competing females, there is potential for more complex signaling strategies than the ones modeled by us (Harari et al 2011). Experimental manipulation of juvenile environments can also prove informative (Gibbs et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological costs of pheromone production are only beginning to become clear (Harari et al 2011;Harari and Steinitz 2013). Even less attention has been paid to the spatial distribution of females (McNeil 1991), how developmental environment affects calling, and how calling neighbors affect a female's calling behavior (Stelinski et al 2006).…”
Section: A Theoretical Approach To Adaptive Variation In Female Pheromentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, various studies found considerable interindividual variation in the amount and ratio of pheromone components [20]. Although such variation can be caused by local environmental factors or due to heterozygote advantage [21], there is certainly the possibility that long-range sex pheromones covary positively with the condition of the sender and serve as reliable indicator of mate quality [22,23], especially if produced and emitted by the less limiting sex (usually the males). More importantly, we know from studies on acoustic signals used to attract conspecific mates that selection on species recognition does not necessarily preclude sexual selection (e.g.…”
Section: Introductionmentioning
confidence: 99%